Legal Protection for Consumers Against Food Label Manipulation in Digital Commerce - Yohana Apriana; Lewiandy Lewiandy (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The rapid growth of digital commerce in processed food products has increased the risk of relabeling and repackaging practices involving misleading information, including health-related claims such as gluten-free, dairy-free, plant-based, and allergy-friendly. Such practices may mislead consumers and pose risks to consumer health and safety. This study aims to analyze the legal framework governing relabeling and repackaging practices in Indonesia and to examine the forms of legal liability imposed on business actors for consumer losses resulting from misleading food information. The research employs a normative legal method using statutory, conceptual, and case-based approaches. The analysis is based on the Consumer Protection Law, the Food Law, and relevant regulations concerning food labeling and safety. The findings indicate that relabeling and repackaging activities are legally permissible only when they comply with applicable requirements related to food safety, labeling accuracy, and consumer protection. Business actors who provide misleading or inaccurate information may be subject to administrative, civil, and criminal liability under the principle of product liability. The study concludes that stronger regulatory oversight and more effective law enforcement are essential to ensuring food safety, promoting transparency in product information, and safeguarding consumer rights in the era of digital commerce.